Mass Spectrometric Analysis of A Bioflocculant Produced from Chicken Waste - Mohammed, Jibrin Ndejiko,; Wan Rosmiza Zana Wan Dagang,; Wahid Ali Hamood Altowayti,; Hamza,; Usman Ibrahim, (Progress in Engineering Application and Technology, 2022)
This work embodies use of a High performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (HPLC - MS QTOF) for the determination of molecular mass of the constituent moieties in a bioflocculant produced through Aspergillus flavus’ fermentation of chicken viscera. The time-of-flight mass spectrometry was conducted with HPLC MS-MS QTOF G6560A, UTM in dual Ion Electrospray Ionization (ESI). The experiment was conducted at gas flow rate 12 L/min, gas temperature 350°C, skimmer cone potential 30 V, fragmentor potential 125 V, Nozzle Voltage 1000 V, mass range 100–3,000 m/z  using 0.1% formic acid and Acetonitrile as the mobile phase. The chromatogram obtained shows many spectra of low and high-level molecular weight constituents with some prominent peaks that appeared in the range of 2.23 to 6.62 minutes having molecular mass of between 180.06 to 678.27 Da. The most profuse peaks were found at mass of 678.27 Da (2.90 min), 646.02 Da (2.92min) and 692.83 Da (3.59min) in the negative ESI indicating high existence of the negative ionized groups in the bioflocculant.  The results also showed the bioflocculant to be composed of few positively charged compounds with +4 and +3 charges. LC- MS QTOF offers an attractive technique for the fast and specific mass measurement of the bioflocculant constituent.